Projection parameters for zirconia-alumina-ceria coatings made by flame spraying from results of numerical simulation (2017)
A numerical simulation was performed with the software Jets et Poudres, the results let choose the parameters to deposit zirconia-alumina-ceria coatings of different composition on substrates of red clay, by thermal spraying with the oxyacetylene flame to obtain homogeneous coatings with good adhesion to the substrate. The effect of the projection distance (7, 10 and 12cm) between the substrate and the torch, the fusion percentage of particles and the K-Sommerfeld number was determined. This number is dimensionless and is affected by the projection distance and by the chemical composition of the particles. For a projection distance of 9cm, the fusion percentage of the particles varies between 83.8% and 100%, and the K-Sommerfeld number between 47.3 and 50 for the different compounds. This makes possible to obtain uniform coatings with good wettability, therefore, good adhesion to the substrate, while for the distance of 7cm the fusion percentage varies between 22% and 38%, due to the short time of the particles in the flame which causes low adhesion, when the projection distance is 12cm the particles do not have sufficient kinetic energy to reach the substrate and therefore the coating is not deposited.